Forty Year Shifting Distribution of Systolic Blood Pressure with Population Hypertension Treatment and Control - Lackland, Daniel T. (Circulation, 2020)
BACKGROUND: Hypertension awareness, treatment and control programs were initiated in the United States (US) during the 1960s and 70s. While blood pressure (BP) control in the population and subsequent reduced hypertension-related disease risks have improved since the implementation of these interventions, it is unclear if these BP changes can be generalized to diverse and high risk populations. This report describes the four-decade change in BP levels for the population in a high disease risk southeastern region of the US. The objective is to determine the magnitude of the shift in systolic blood pressure (SBP) among blacks and whites from the Southeast between 1960 and 2005 with the assessment of the unique population cohorts. METHODS: A multi-cohort study design compared BPs from the Charleston Heart Study (CHS) and Evans County Heart Study (EHS) in 1960, and the REasons for Geographic And Racial Differences in Stroke (REGARDS) four decades later. The analyses included participants 45 years and older from CHS (n=1323), ECS (n=1842), and REGARDS (n=6294) with the main outcome of SBP distribution. RESULTS: Among whites aged 45-54 years, the median SBP was 18 mmHg (95% CI: 16 – 21 mmHg) lower in 2005 than 1960. This median shift 45 mmHg (95% CI: 37 – 51 mmHg) decline for those aged 75+ years. The shift was also larger for blacks with median declines of 38 mmHg (95% CI: 32 – 40 mmHg) at age 45-54, and 50 mmHg (95% CI: 33 – 60 mmHg) for ages 75+. The 95th percentile of SBP decreased 60 mmHg for whites and 70 mmHg for blacks. CONCLUSIONS: The results of these current analyses of the unique cohorts in the Southeast confirm the improvements in population SBP levels since 1960. This assessment provides new evidence of improvement in SBP suggesting that strategies and programs implemented to improve hypertension treatment and control have been extraordinarily successful for both blacks and whites residing in a high risk region of the US. Severe BP elevations commonly observed in the 1960s have been nearly eliminated, with the current 75th percentile of BP generally less than the 25th percentile of blood pressure in 1960.